Protocol of a randomised controlled trial of real-time continuous glucose monitoring in neonatal intensive care 'REACT'. Issue 6 (4th June 2018) - Beardsall, Kathryn; Thomson, Lynn; Guy, Catherine; van Weissenbruch, Mirjam M; Iglesias, Isabel; Muthukumar, Priya; Somisetty, Sateesh Kumar; Bond, Simon; Petrou, Stavros; Dunger, David
Abstract : Introduction: Hyperglycaemia is common in the very preterm infant and has been associated with adverse outcomes. Preventing hyperglycaemia without increasing the risk of hypoglycaemia has proved challenging. The development of real-time continuous glucose monitors (CGM) to inform treatment decisions provides an opportunity to reduce this risk. This study aims to assess the feasibility of CGM combined with a specifically designed paper guideline to target glucose control in the preterm infant. Methods and analyses: The Real Time Continuous Glucose Monitoring in Neonatal Intensive Care (REACT) trial is an international multicentre randomised controlled trial. 200 preterm infants ≤1200 g and ≤24 hours of age will be randomly allocated to either real-time CGM or standard care (with blinded CGM data collection). The primary outcome is time in target 2.6–10 mmol/L during the study intervention assessed using CGM. Secondary outcomes include efficacy relating to glucose control, utility including staff acceptability, safety outcomes relating to incidence and prevalence of hypoglycaemia and health economic analyses. Ethics and dissemination: The REACT trial has been approved by the National Health Service Health Research Authority National Research Ethics Service Committee East of England (Cambridge Central); Medical Ethics Review Committee, VU University Medical Centre, Amsterdam, The Netherlands and the Research Ethics Committee, Sant Joan de Déu Research Foundation, Barcelona, Spain. Recruitment began in July 2016 and will continue until mid-2018. The trial has been adopted by the National Institute of Health Research Clinical Research Network portfolio (ID: 18826) and is registered with anInternational Standard Randomised Control Number (ISRCTN registry ID: 12793535). Dissemination plans include presentations at scientific conferences, scientific publications and efforts at stakeholder engagement. Trial registration number: ISRCTN12793535; Pre-results.